Maleated soybean oil as coupling agent in recycled polypropylene/wood flour composites: Mechanical, thermal, and morphological properties. (August 2019) - Poletto, Matheus
In this study, composites with interesting mechanical and thermal properties were prepared using chemically modified vegetable oil as coupling agent in wood-fibers-reinforced recycled polypropylene. Soybean oil was reacted with maleic anhydride to produce maleated soybean oil (MASO). The mechanical, thermal, and morphological properties of the composite were evaluated. The usage of MASO as a coupling agent clearly improved the interfacial adhesion between wood fibers and the polypropylene matrix and increased the mechanical and thermal properties evaluated. Based on the obtained results, it is concluded that MASO can act as an alternative source of coupling agent dispensing with the addition of petroleum-based compatibilizers to improve the mechanical and thermal properties of composites reinforced with natural fibers.